Improving PAI Online Learning Outcomes with Bookwidgets as a Media during the Covid-19 Pandemic - Nugraha, Dera; Handayani, Fitri; Zaqiah, Qiqi Yuliati (Universitas Muhammadiyah Magelang, 2021)
Islamic Religious Education (PAI) learning that conducted online during the Covid-19 pandemic had an impact on low learning outcomes. Organizing effective learning online was a challenge for Islamic Education teachers. After Islamic Education teachers learn and use Book widgets as a learning medium, the attendance and learning outcomes of students increase significantly. This study aims to determine the increase in attendance and learning outcomes of students in online Islamic Education learning specifically about fasting topic with the Book widgets learning media. The subjects in this study were 47 students of Islamic education and class VII-a and VII-e students, consisting of 22 male students and 25 female students. The classroom action research method was carried out in two cycles. Data collection techniques were carried out by writing techniques and interviews. The collected data were then analysed using descriptive analysis techniques by comparing the results between the initial data, cycle I and cycle II. The results of this study indicated a significant increase in attendance and learning outcomes of students. The attendance of students was 84% initially, to 96% in cycle I, and 100% in cycle II. The average learning outcomes of students in pre-cycle 76 became 87 in cycle I, and 96 in cycle II.